Dear Sweet Pea - Murphy, Julie, 1985- (Balzer + Bray, 2019)
Thirteen-year-old Patricia "Sweet Pea" DiMarco navigates her parents' divorce after they decide to live in nearly identical houses just two doors away from each other. Between them is eccentric advice columnist Miss Flora Mae who befriends the young Sweet Pea. One day, Flora goes on vacation and asks Sweet Pea to send out her letters for the column. However, Sweet Pea sees a letter with familiar handwriting, and what she does with that letter has unexpected consequences.